SEDIAAN KRIM TABIR SURYA FRAKSI ETIL ASETAT KULIT BATANG RAMBUTAN, AKTIVITAS ANTIOKSIDANNYA - Tisa Mandala Sari; Noni Rahayu Putri; Silvia Asnita Sari (JURNAL KATALISATOR, 2023)
Research has been carried out on the determination of antioxidant activity in vitro on rambutan bark with experimental methods. The ethyl acetate fraction was obtained from the ethanol extraction of the rambutan bark from maceration. The formula was made by varying the concentration of 3 fractions, namely F0 without fraction, F1 (1%), F2 (1.5%), and F3 (2%) with organoleptic test parameters, each formula was in the form of a semi-solid, distinctive odor and different color. -different in white F0, orange F1, light brown F2 and brown F3. Homogeneity test on each homogeneous formula, viscosity test results obtained 2840cP, 2825cP, 2815cP, 2810cP for F0, F1, F2 and F3 respectively. The washing power test was found to be 32mL; 32.1mL; 30.5mL; 27.1mL for F0, F1, F2 and F3 respectively. The cream type test on each formula showed the W/A type. pH test results obtained 7,10; 7.14; 7.06; 6.97 for F0, F1, F2 and F3 respectively. Stability test on each formula showed stable results, irritation test on each formula showed that no irritation occurred. Determination of antioxidant activity using the DPPH method by looking at the IC50 value and determining the SPF value. The results of the antioxidant activity test obtained IC50 values ​​at F0 of 108.497 ppm in the medium category, F1 at 69.23 ppm in the strong category, F2 at 61.92 in the strong category, and F3 at 61.39 in the strong category. The best formula was formula 3 with antioxidant activity of 61.39 ppm in the strong category.